Guidelines for reporting zircon Hf isotopic data by LA-MC-ICPMS and potential pitfalls in the interpretation of these data - Fisher, Christopher M.; Vervoort, Jeffery D.; Hanchar, John M. (Chemical geology, 2014)
High quality analytical data are essential for the development of sound scientific interpretations. To ensure the quality of the data published in Chemical Geology, a new type of contribution has been introduced - the "Invited Technical Paper". When a particular technical issue needing discussion or clarification is identified, specialists in the technique will be invited to share their expertise. As is true for all articles published in the journal, these contributions will be subject to peer review before publication. The first topic to be treated concerns in situ Hf isotopic measurements in zircon by laser ablation inductively coupled plasma mass spectrometry. This is an extremely powerful and promising technique that has been adopted by many laboratories throughout the world. However, if insufficient care is taken during analysis and data processing, inaccurate results can be obtained, notably because of the existence of very large isobaric interferences on the isotope of interest. To address this issue, we have asked Christopher Fisher, Jeffery Vervoort and John Hanchar to provide a set of guidelines that can be adopted to assure that reliable Hf isotopic data are obtained by this technique. Abstract Over the past decade, the Hf isotope composition of zircon, as determined in situ by laser ablation-multicollector-inductively coupled plasma mass spectrometry (LA-MC-ICPMS), has been applied increasingly to a wide range of geological problems and has proven to be a valuable analytical tool. There has been no uniformity, however, in the reporting of in situ Hf isotopic data and, quite often, reviewers and readers of papers are not provided with sufficient information to assess data quality. The goal of this invited contribution is to provide the non-specialist with a brief outline and explanation of what is required for proper presentation and documentation of in situ Hf isotopic data from zircon, including details of how the challenging large isobaric interference corrections have been made. In addition, we discuss a number of potential pitfalls vis-à-vis the assignment of the incorrect age to the measured Hf isotope composition. Non-specialists should be aware of these important issues when doing their own analyses and evaluating the analyses done by others. •Suggested requirements for reporting Hf isotope data in zircon by LA-MC-ICPMS•We emphasize the importance of analyzing standard zircons with wide range of REE/Hf.•Problems associated with incorrect age assignment are discussed.